PERBANDINGAN PENGGUNAAN MODEL PEMBELAJARAN SCRAMBLE DAN PROBING PROMTING TERHADAP HASIL BELAJAR SISWA KELAS IX PADA MATA PELAJARAN IPS DI SMP NEGERI 6 KOTA JAMBI - Pratiwi Indah Sari (Universitas Batanghari Jambi, 2018)
Abstract The purpose of this research is to know the picture, the influence and the comparison between the use of the learning model of scramble and the probing promting on the result of student learning of class IX on IPS subjects in SMP Negeri 6 Kota Jambi. The research design used is quantitative research with quasi experimental method. Based on the result of research, it can be concluded that there is a comparison of the acquisition of student learning outcomes by using the model of learning scramble and probing promting. Where, student learning outcomes using probing promting learning model is superior because students feel more challenged and courageous and confident to express their own opinions based on their own assumptions. Keyword : Learning Model, Scramble, Probing Promting, Learning Outcomes.